S SOCIETY'S PERCEPTION OF MARRIAGE NYEROD IN KERAMAS VILLAGE, DISTRICT BLAHBATUH GIANYAR DISTRICT: SOCIETY'S PERCEPTION OF MARRIAGE NYEROD IN KERAMAS VILLAGE, DISTRICT BLAHBATUH GIANYAR DISTRICT - Padmawati, Gusti; Arini, Ni Wayan; Indrayani, A.A. Diah (UHN IGB Sugriwa Denpasar, 2025)
Nyerod marriage is one of the typical Balinese marriage traditions which is full of cultural meaning and traditional values. In the midst of modernization, this tradition is facing challenges in the form of changes in public perception, especially among the younger generation who do not understand the traditional values behind this tradition. This research aims to reveal people's perceptions of Nyerod marriage in Keramas Village, Blahbatuh District, Gianyar Regency, and understand its relevance in the modern era. A qualitative approach using in-depth interviews and observation methods was used to explore the community's views, including the reasons for preserving traditions and the influence of modernization on their understanding. The research results show that the Nyerod tradition is seen as a symbol of family loyalty and eternity, but its meaning has shifted due to the influence of education, media and globalization. Patriarchal cultural factors also influence the maintenance of this tradition, although there are changes in values in the younger generation who are more critical of gender roles. This research provides new insights into the socio-cultural dynamics in Bali and how local traditions adapt to developments over time. It is hoped that these findings can become a reference in preserving local culture in harmony with social change, as well as strengthening literature on cultural change in traditional Balinese society. Keywords : Nyerod marriage, Balinese culture, community perception, modernization, Keramas Village.